Plang Edukasi Sampah Sebagai Sarana Edukasi Dan Media Di Kelurahan Pematang Gubernur - Roy Syahputra; Zulia Sulistiani; Monika Aprianti; Muhammad Hogo; Febry Kansa; Rina Trisna Yanti; Tita Septi Handayani; Mujiono Mujiono (Jurnal Dehasen Mengabdi, 2026)
Waste management, particularly non-biodegradable waste, remains a major environmental problem in densely populated residential areas, including Pematang Gubernur Subdistrict, Bengkulu City. Low public awareness of proper waste disposal and management has led to environmental pollution, clogged drainage systems, and decreased environmental quality and public health. This community service activity aimed to increase public knowledge and awareness regarding types of waste and the time required for waste decomposition through the use of educational signboards as visual information media. The methods applied in this program included field observation, design and production of educational signboards, and installation of the signboards at strategic locations prone to illegal waste disposal. The educational signboards were designed with simple and clear visual content to ensure that the information could be easily understood by all community members. The results of the activity indicated a positive response from the community, as residents showed increased attention to the information displayed on the signboards and a better understanding of the long-term environmental impacts of waste. The presence of educational signboards proved to be an effective and sustainable educational medium that contributed to encouraging positive behavioral changes toward better and more sustainable waste management practices.